Chapter Presentazione - Graziani, Michela (Studi di Traduzione Letteraria Lusofona, 2022)
This miscellaneous volume aims to present for the first time, in Italian language, the collection of short stories A China fica ao lado / La Cina è accanto by the Portuguese writer Maria Ondina Braga, concerning the Chinese migration flows to Macao in the '60s of the past century. The collection was published for the first time in Lisbon in 1968 and translated for the first time in Chinese language in Macao in 1991.